Emerging SARS-CoV-2 variants: Why, how, and what's next? - Chen, Yu; Liu, Qianyun; Zhou, Li; Zhou, You; Yan, Huan; Lan, Ke (Cell insight, 2022)
The emergence of the SARS-CoV-2 Omicron variant poses a striking threat to human society. More than 30 mutations in the Spike protein of the Omicron variant severely compromised the protective immunity elicited by either vaccination or prior infection. The persistent viral evolutionary trajectory generates Omicron-associated lineages, such as BA.1 and BA.2. Moreover, the virus recombination upon Delta and Omicron co-infections has been reported lately, although the impact remains to be assessed. This minireview summarizes the characteristics, evolution and mutation control, and immune evasion mechanisms of SARS-CoV-2 variants, which will be helpful for the in-depth understanding of the SARS-CoV-2 variants and policy-making related to COVID-19 pandemic control.